2000 SONRASI TÜRK ROMANINDA TASAVVUFİ SÖYLEM - TOKİZ, ONUR (Fırat Üniveristesi, 2011)
Yirmi birinci yüzyılla birlikte tasavvuf, Türk romanında önemli bir yer tutar. Bu çalışmada tasavvufi söylemin Türk romanına etkileri incelendi. Geniş bir roman taramasından sonra belirlenen İhsan Oktay Anar'ın `Suskunlar', Elif Şafak'ın `Aşk', Ahmet Ümit'in `Bab-ı Esrar' ve Nazan Bekiroğlu'nun `Lâ' isimli eserleri çalışmanın temeline oturtuldu.İki bölüm halinde düzenlenen çalışmanın ilk bölümünde, tasavvufi söylem ve bu söylemin Türk romanına etkileri, Tanzimat'tan günümüze gelerek incelendi.Çalışmanın ana bölümü olan ikinci bölümde romanların, yapısal ve izleksel tahlili yapıldı. Bu tahlil esnasında, özellikle tasavvuf disiplininden yararlanıldı. Ayrıca; tarih, sosyoloji, felsefe, psikoloji, dinler tarihi ve güzel sanatların imkânları da çalışmaya yansıtıldı. Böylece romanlardaki tasavvufi söylemin mahiyeti ve işleniş şekilleri ortaya konuldu.

Sufism gained an important place in Turkish Novel by the 21st century. In this study, the impacts of mystical expression to the Turkish Novel were investigated. Ihsan Oktay Anar?s `Suskunlar?, Elif Safak?s `Ask?, Ahmet Umit?s `Bab-i Esrar? and Nazan Bekiroglu?s `La? were established as the fundemantals of the study after a wide novel review.The work was constructed in two chapters, in the first chapter, the mystical expression and its impacts upon Turkish Novel were investigated since the Tanzimat Period up to today.In the second chapter, which is the main part of the study, the structural and thematic analysis of the novels were studied. Throughout this analysis, the Sufism Discipline was referred specifically. Besides, the potentialities of History, Philosophy, Psychology, History of Religions and Fine Arts were also reflected to the study. Thus, the essence and how the writer treated a subject in the novel written with a mystical expression were presented.
Mystical expression in post 2000 Turkish novel
Keywords: Türk Dili ve Edebiyatı